Injury fear in mountaineering accidents: a study of Turkish mountaineers’ experiences - Erdoğan Ekinci; Fatih Mehmet Parlar; Özge Ercan; Nedim Tekin; Begüm Yaşar Sönmez; Ümit Doğan Üstün (BMC Sports Science, Medicine and Rehabilitation)
Abstract Aim Mountaineering, which involves high levels of risk and challenge, is an extreme sports activity with a deep history, requiring superior physical fitness, mental strength and technical knowledge. The high level of risk inherent in mountaineering also brings with it injuries, which negatively affect athletes’ performance and lead to traumatic experiences that cause anxiety. This research aims to examine in depth the injury concerns of licensed mountaineers. Method The present research conducted as a qualitative study with the phenomenological approach and the data were obtained through in-depth interviews conducted face-to-face. In the interviews conducted with 12 professional mountaineers selected with the criterion sampling method, an interview form consisting of semi-structured questions developed by the research team based on Lazarus’ Cognitive-Motivational-Relational Theory was used. The obtained data were analyzed with the content analysis technique. Results The research results reveal that the injury concerns of mountaineers are related to the themes of risk management, psychological resilience, mental strengthening and strategic thinking in the cognitive dimension; amotivation, passion and taking precautions in the motivational dimension; and resistance, environmental support, environmental pressure, developing self-awareness and persuasion in the relational dimension. Conclusion These results show that the performance of athletes in the Cognitive-Motivational-Relational dimensions is affected by injury fear. Therefore, it shows that injury fear is a critical factor that must be taken into consideration and managed in order to ensure sustainability in mountaineering.